Papel y Evolución de las Instituciones en la Dinámica Económica Salvadoreña 1979-2008: Una mirada evolucionista e histórica - Guzmán López, Karla (2015)
In this paper we will analyze the most significant historical changes in economic and institutional areas which took place in El Salvador, showing the relationship causal between them. Research was done around years 1980 – 2008, because it was an ideal period to study from a historical and evolutionist perspective, the changes happened in El Salvador, advantaged and disadvantaged sectors and type of economic dynamics influenced by the policies implemented. This with objective to provide relevant information to give prominence to the role of institutions in the socioeconomic history, often omitted from economic analysis, however the importance of institutions to economic spectrum Salvadorian were determinants during period of study. The current model has been a reflection of institutional changes with some teleological features and historical factors.